Análise do comportamento mecânico de juntas soldadas de aço inoxidável AISI 304 aplicando a técnica de correlação digital de imagens - Costa, Ycaro Jorge Maia da (Universidade Federal Rural do Semi-Árido, 2018)
The thermal gradient of welded joints promotes the modification of its microstructure, subdividing it into three mechanically distinct regions: Weld Metal (MS), Heat Affected Zone (ZAC) and Base Metal (MB). The intensity of the welding parameters as well as the thermal input applied in welding influences the joint cooling rate in the ZAC, a characteristic region due to the increase in associated ductility due to the phenomenon of recrystallization and grain growth. The present work used the Digital Image Correlation technique, which, through the progressive recording of images during a tensile test, compares different stages of deformation of the treated surface of the specimen, identifying displacement and deformation fields, mechanical properties and evolution of the deformation of each area mentioned. Among the results, ZAC welded joints with Welding Energy (ES) of 10.5 kJ / cm showed a ductility increase about 60% higher than its MB, while with ES of 9.9 kJ / cm this increase was 48%.
Monografia
Keywords: Correlação Digital de imagens CDI; Soldagem MIG; Aço inoxidável AISI 304; Ensaio de Tração; Propriedades mecânicas; Digital Image Correlation DIC; GMAW welding; Stainless steel AISI 304; Tensile test; Mechanical properties; ENGENHARIAS::ENGENHARIA MECANICA